Marketing para jovens consumidores de café: estratégias para o mercado brasileiro - Sette, Ricardo de Souza (1999)
Enterprisesof different sectors, within the new competitive structure, aware of the importance ofrneeting the consumer,sneeds has been causing changes-both in the population'sconstumes and habits. New foodsand new ways of distribuition have been introduced, accompanied by aggressive advertising plans. The coffee sector, relying upon .its.tradition has not kept pace with the rhytm of modernization and marketing of the beverage sector presenting, asa significant-Ioss of sharing in themarket and reduced-consumption. This work aims to know the young consumer of coffee in Brazil and to suggest marketing strategies which can stimulate him to consume the product further. Bymeans of fQCUSgroupstechnique were performed qualitative studies in the city of São Paulo and quantitative studies in the cityof Belo -Horizonte. Analysed the .results and by identifying the meaning of coffee to this young public, generical strategies which contributed to increased coffee consumption in horne market were presented. The results showed that, among the young university students,- a negative image concerning coffee predominates. Highly associated with cigarrette and vice, 54% of the interviewees has-not the habitof taking coffee in addition to associating the coffee image toan adult, who works- hard, very stressedand full of responsabilities. Who takes it, has learnt with the family as a habitor at work. As . positive aspects, they regardcoffee as a stimulant-andmuch associatedwith a break, rest and relaxo They think that coffee still holds its traditional status, it is not a practical product suitable for the young as the advertisiment does not taIk to the young. Marketing strategies designed having in mind the future coffee consumer should fmd out the values which guide today's young people's concems to build products, packages and ways of consumption and communication which makesense in their world. Because this worldisdifferent from thatwhere coffee has or had its honor place: the Brazilian home. The way as it has been realized by the young today, it follows that it is needed to change if one wants to stay